Recombinant Protein Filovirus Vaccines Protect Cynomolgus Macaques From Ebola, Sudan, and Marburg Viruses - Lehrer, Axel T.; Chuang, Eleanore; Namekar, Madhuri; Williams, Caitlin A.; Wong, Teri Ann S.; Lieberman, Michael M.; Granados, Alex; Misamore, John; Yalley-Ogunro, Jake; Andersen, Hanne; Geisbert, Joan B.; Agans, Krystle N.; et al. (Frontiers in Immunology, 2021)
Ebola (EBOV), Marburg (MARV) and Sudan (SUDV) viruses are the three filoviruses which have caused the most fatalities in humans. Transmission from animals into the human population typically causes outbreaks of limited scale in endemic regions. In contrast, the 2013-16 outbreak in several West African countries claimed more than 11,000 lives revealing the true epidemic potential of filoviruses. This is further emphasized by the difficulty seen with controlling the 2018-2020 outbreak of EBOV in the Democratic Republic of Congo (DRC), despite the availability of two emergency use-approved vaccines and several experimental therapeutics targeting EBOV. Moreover, there are currently no vaccine options to protect against the other epidemic filoviruses. Protection of a monovalent EBOV vaccine against other filoviruses has never been demonstrated in primate challenge studies substantiating a significant void in capability should a MARV or SUDV outbreak of similar magnitude occur. Herein we show progress on developing vaccines based on recombinant filovirus glycoproteins (GP) from EBOV, MARV and SUDV produced using the Drosophila S2 platform. The highly purified recombinant subunit vaccines formulated with CoVaccine HTTM adjuvant show an excellent safety profile and elicit potent immune responses in mice, guinea pigs and non-human primates (NHPs) and consistently produce high antigen-specific IgG titers. Three doses of an EBOV candidate vaccine elicit full protection against lethal EBOV infection in the cynomolgus challenge model while one of four animals infected after only two doses showed delayed onset of Ebola Virus Disease (EVD) and eventually succumbed to infection. The monovalent MARV or SUDV vaccine candidates completely protected cynomolgus macaques from infection with lethal doses of MARV or SUDV. It was further demonstrated that combinations of MARV or SUDV with the EBOV vaccine can be formulated yielding bivalent vaccines retaining full efficacy. The recombinant subunit vaccine platform should therefore allow the development of a safe and efficacious multivalent vaccine candidate for protection against Ebola, Marburg and Sudan Virus Disease.